Lernaeocera lusci (Copepoda: Pennellidae) on bib (Trisopterus luscus) from Southampton Water. - Evans, N.A., P.J. Whitfield, R.N. Bamber & P.M. Espin (Parasitology, Cambridge, 1983)
O-group bib, Trisopterus luscus caught on the cooling water intake screens of Fawley Power Station in March and April 1982 were infected (prevalence = 34·8%; intensity = 1·65/infected fish) with adult females of the pennellid parasitic copepod Lernaeocera lusci. The bib sample of 293 fish was divided, for analysis, into 5 length classes. In each of these the level of parasitization with L. lusci was broadly similar and in all 5 classes the parasite population was over-dispersed. Of the living copepods on T. luscus, 93% possessed egg strings while the remaining 7% consisted of earlier developmental stages. The majority of the parasites were attached to gill arches and here they exhibited distinct microhabitat and orientation preferences. A 3–2–4–1 descending order of gill arch utilization was apparent and copepods were non-randomly distributed along the dorso-ventral axis of gill arches with medial and ventral sectors being more heavily used than dorsal ones. An analysis was carried out on the body and egg string wet weights of parasites removed from fish harbouring different parasite densities. As copepod density increased neither the mean parasite body weight nor egg string weight altered significantly. Length/weight relationships of uninfected and infected fish were remarkably similar and thus provided no evidence that L. lusci has a marked effect on the condition of O-group T. luscus. The study demonstrated a significant positive association between infection with L. lusci and heavy infections with metacercarial cysts of Cryptocotyle lingua.